2022
DOI: 10.1186/s12887-022-03156-x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal, neonatal, developmental and demographic predictors of intelligence at 4 years of age among low birth weight children: a panel study with a 2-year follow-up

Abstract: Intoduction Childhood intelligence is an important predictor of later outcomes in life such as socioeconomic status or health. Hence, a deeper understanding of predictors of child intelligence should suggest points of intervention for children facing adversities. Objectives The purpose of this study is to examine the predictive value of demographic, perinatal and neonatal variables after birth and developmental characteristics at age 2 for 4-year i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In our previous studies, we found that gestational age and birth body weight played important roles in the risk of these dysfunctions [ 19 ]. Likewise, previous studies have also reported that birth weight or gestational age were associated with intelligence [ 28 , 29 , 30 , 31 ] and attention deficits [ 28 , 32 , 33 , 34 ], Other perinatal and postnatal factors can also correlate with children’s cognitive development.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In our previous studies, we found that gestational age and birth body weight played important roles in the risk of these dysfunctions [ 19 ]. Likewise, previous studies have also reported that birth weight or gestational age were associated with intelligence [ 28 , 29 , 30 , 31 ] and attention deficits [ 28 , 32 , 33 , 34 ], Other perinatal and postnatal factors can also correlate with children’s cognitive development.…”
Section: Introductionmentioning
confidence: 82%
“…Although the assessments of this study can be comprehensive, it still had limitations. First, we did not analyze the impact of social and environmental factors on children’s cognitive development, such as mother’s education level or household income, which have been reported to relate to children’s cognition [ 28 ]. Second, not all participants received K-CPT and the ophthalmic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental surveillance should consider appropriate timing and intervals in terms of cost-effectiveness and availability of healthcare resources. If NICU graduates have more severe risk factors, they would be at an even higher risk of various developmental problems [10][11][12]. Several risk factors that must be evaluated during NICU stay are summarized in Table 1 for clinicians not to delay neurodevelopmental evaluation for referral to the Department of Pediatric Rehabilitation Medicine.…”
Section: Early Neurodevelopmental Assessment Planmentioning
confidence: 99%
“…According to the numbers and grades of risk factors (Table 1), a corrected age (CA) to visit for neurodevelopmental surveillance and follow-up periods are suggested in Fig. 1 [3,5,10,13,14].…”
Section: Early Neurodevelopmental Assessment Planmentioning
confidence: 99%
See 1 more Smart Citation